2021
DOI: 10.1051/bioconf/20213005005
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological potential of fungi and bacteria with ligninolytic activity (mini-review)

Abstract: The presented mini-review gives a general idea of oxidative enzymes of fungi and bacteria. Possible directions of their practical application are shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The screening included four WRF, well-studied by the group (Palli et al, 2017;Jaeń-Gil et al, 2019;Beltrań-Flores et al, 2021;Tan et al, 2023), but also two Ascomycota fungi. These Ascomycota fungi, selected from the Trichoderma and Aspergillus genera, also produce extracellular ligninolytic enzymes (laccase and peroxidases) (Dhakar et al, 2015;Kurkina et al, 2021), have demonstrated high efficiency in removing contaminants (Tripathi et al, 2013;Mukherjee, 2016), and possess a range of other enzymes such as oxidases, cellulases, xylanases, and amylases, which could potentially contribute to the degradation of either the OPFRs or other complex constituents in wastewater. The evaluation of these fungal candidates could allow the future use of a mixed consortium for wastewater treatment, promoting a co-culture approach that enhances enzymatic activities and promotes contaminant removal (Lira-Peŕez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The screening included four WRF, well-studied by the group (Palli et al, 2017;Jaeń-Gil et al, 2019;Beltrań-Flores et al, 2021;Tan et al, 2023), but also two Ascomycota fungi. These Ascomycota fungi, selected from the Trichoderma and Aspergillus genera, also produce extracellular ligninolytic enzymes (laccase and peroxidases) (Dhakar et al, 2015;Kurkina et al, 2021), have demonstrated high efficiency in removing contaminants (Tripathi et al, 2013;Mukherjee, 2016), and possess a range of other enzymes such as oxidases, cellulases, xylanases, and amylases, which could potentially contribute to the degradation of either the OPFRs or other complex constituents in wastewater. The evaluation of these fungal candidates could allow the future use of a mixed consortium for wastewater treatment, promoting a co-culture approach that enhances enzymatic activities and promotes contaminant removal (Lira-Peŕez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%